Validity of a commercial GNSS-IMU system in temporal biathlon range work analysis - Köykkä, M.; Ruotsalainen, K.; Vierola, S.; Vänttinen, T.; Ohtonen, O.; Linnamo, V. (Book of Abstracts. 4th Nordic Winter Sports Conference "Performance in snow sports: Translating science into practice" 3rd-4th October, 2022, Mid Sweden University, Campus Östersund, Sweden, 2022)
The aim of this study was to examine the validity of a wearable commercial GNSS-IMU system (Archinisis) in automated temporal biathlon range work analysis. Twelve biathletes skied twelve laps around the shooting range and performed six times a 5-shot set of biathlon shooting from the prone and standing postures. Temporal biathlon range work characteristics were simultaneously collected using the wearable system and a high-speed video camera. The wearable system detected all events that were obtained from the camera footage. In prone shooting, significant differences (Camera-Archinisis) were observed in approaching (-0.43 ± 0.37 s), shot intervals (-0.003 ± 0.006 s), total shooting (-0.01 ± 0.02 s), mat off (-0.09 ± 0.17 s), leaving (0.44 ± 0.33 s), range (-0.11 ± 0.18 s) and mat (-0.10 ± 0.29 s) times (all p < 0.01). No difference was observed in preparing time (0.00 ± 0.25 s). In standing shooting, significant differences were observed in preparing (-0.20 ± 0.28 s), shot intervals (-0.007 ± 0.012 s), total shoot ing (-0.03 ± 0.04 s), mat off (0.07 ± 0.18 s), leaving (0.19 ± 0.29 s) and mat (-0.16 ± 0.30 s) times (all p < 0.01). Differences in approaching (-0.08 ± 0.36 s) and range (-0.03 ± 0.19 s) times were not significant. Strong relationships (rs from 0.87 to 1.00, all p < 0.001) between the methods were observed for all variables. Small absolute differences indicate that the Archinisis system can be used to automatically collect and analyze temporal biathlon range work characteristics with reasonable accuracy